The Development of Rotary Fixture on Laser Engraver Machine - Rachmad Hartono; Demas Cahyadi Ningrat; Fahru Rozi; Farhan Ali Husaini (Integrated Mechanical Engineering Journal, 2025)
In the Mechanical Engineering Laboratory of Pasundan University there is a laser engraver machine that is able to perform the gravir process on materials that have a flat surface. The laser engraver has the disadvantage of not being able to do the gravir process on cylindrical workpieces. To overcome this weakness, it is necessary to make a workpiece holder tool specifically for holding cylindrical workpieces. The purpose of this research is to improve the ability of the laser engraving machine, so a rotary fixture model is made on the laser engraver machine. The rotary fixture is directly connected to a stepper motor. The stepper motor is controlled by the axis controller on the laser engraving machine. The rotary fixture has been successfully made and has undergone a testing process. The letter gravir process produced on a cylindrical gravir surface with workpiece dimensions Ø66 mm with a workpiece thickness of 6 mm requires a power modulation of 250 and an engraving speed of 200 mm/min and produces gravir with a letter width of 16 mm, a letter height of 5.50 mm and a spacing distance of 9.50 mm stated with ideal results. In general, the rotary fixture has been successfully made and improves the performance of the laser engraver machine to perform the gravir process on cylindrical workpieces. From the test results it can be concluded that the rotary fixture mechanical sistem can be operated to gravir letters, names, and batik motifs. With the rotary fixture, it is hoped that craftsmen can increase creativity in carrying out the gravir process using laser engraver.